Farmer response and awareness on soil health cards under Viksit Krishi Sankalp Abhiyan (VKSA) in Amritsar district of Punjab, India - BHATT, RAJAN; ARORA, SANJAY; SHEORAN, PARVENDER; SINGH, BIKRAMJIT (Journal of Soil and Water Conservation, 2026)
The Viksit Krishi Sankalp Abhiyan (VKSA), carried out from 29.05.2025 to 12.06.2025, aimed to raise respondent awareness on climate-smart agricultural techniques, focusing on soil health cards (SHCs). Using raised hand counts, 2250 respondents were asked two sets of ten SHC awareness-based questions during VKSA camps. Correlation analysis and heat maps were used for analysis. Analysis revealed that in Attari, 66% respondents were aware of SHC benefits. However, 79.3% of Sarangdev, 70% of Bhattike, and 74% of Mucchal considered SHC effective. 67.3% of Shamnagar respondents obtained SHC reports after sowing, whereas 74.7% of Chamiari were uncertain about fertilizer use. 71.3% and 75.3% of respondents in Dhade and Kambo, respectively, mentioned issues with SHC training and distribution. Correlation analysis revealed that “awareness about SHC” has a moderate positive relationship with “remedial recommendations” (r =0.33) and “preventing fertilizer overuse” (r = 0.35). A positive correlation (r=0.50) between “crop-wise fertilizer plan” and “reduced cost of cultivation” highlights SHC’s economic impact. However, SHC awareness negatively correlates with “information on SHC” (r = -0.65) and “reduced production costs” (r = -0.42). Additionally, long intervals (r=0.51), awareness of SHC use (r=0.52), and distance (r=0.38) affect SHC efficiency. After discussing the constraints of judicious and climatesmart chemical fertilizer use, SHCs were found to be necessary to abate cultivation costs and upsurge the soil health in the region.